Emergency of Oenocarpus bacaba seedlings from different locations in the state of Pará (Research, Society and Development, 2023)
The emergence of O. bacaba seedlings was evaluated using seeds from different locations in the State of Pará. The samples were obtained from three mesoregions: 1) 25 of Baixo Amazonas, Terra Santa – PA (02º 06' 16" S, 56º 29' 15" W); two); 18 in Northeast Pará, Baião – PA (02º 047' 35" S, 49º 39' 46" W); and two in Southeast Pará, Marabá – PA (05º 21' 54" S, 49º 07' 24" W). 100 fruits were pulped and the seeds sown in a completely randomized design with 45 treatments, two replications and a plot of 50 seeds. Six characters related to seedling emergence were evaluated, with daily monitoring. Data were subjected to analysis of variance and means compared using the Scott Knott test (P≤0.05). The 45 samples showed significant differences for five of the six evaluated characters, demonstrating different behaviors. The means for the characters DIE, DE, DFE, PE, IVE and TME were 25.7 days; 33.9 days, 59.6 days, 74%, 0.7 and 40.4 days, respectively. The means comparison test detected the formation of two (DIE, DE, IVE and TME) and four (PE) of distinct groups. The emergence of O. bacaba seedlings from different origins in the State of Pará presents a different behavior for most of the characters, with the percentage of emergence being the most discriminating character, and at the level of origin only the character days to start of emergence.